False Assumptions of the Problem of Personal Identity. From Personal to Narrative Identity - Betancur, Marta Cecilia (Estudios de Filosofía, 2005)
This paper takes up again the problem of “personal identity” in order to show that the way it has been put leads to a dead end or to an insoluble antinomy: whether the “self” is accepted as a metaphysical entity, a permanent substance, a thing, a conscious substance or an immaterial “self” lodged in the body, or, on the contrary, an entity like this is denied and rejected as a metaphysical phantom. Another intention of the work to demonstrate that the dilemma originates in a wrong exposition of the problem, supported on false assumptions deeply rooted in philosophy and accepted since Modernity. Such assumptions are: substantialism and cosification, psychophysic parallelism and the egocentric perspective. Finally, we present and analyze the solution offered by Ricoeur through “narrative identity”.